Leisure-time Physical Activity of Polish White-collar Workers: A Cross-sectional Study - Agnieszka Nawrocka; Arkadiusz Mynarski; Jarosław Cholewa; Wiesław Garbaciak (SAGE Publishing, 2017)
Objective/background: The aim of this study was to assess the leisure-time physical activity of Polish white-collar workers in relation to various health recommendations. Methods: The study used a cross-sectional design with a convenience sample of 482 white-collar workers from Poland. Researchers recorded the leisure-time physical activity logs for 7 consecutive days of the week. Physical activity level was interpreted in relation to the World Health Organization and the American College of Sports Medicine recommendations. Results: Among the workers, 42% of women and 53% of men declared moderate physical activity for at least 150 minutes per week, but only 23% of women and 18% men undertook activity in at least 5 days. Conclusion: The results of the physical activity identified were significantly different from the American College of Sports Medicine and World Health Organization recommendations. The lower percentage of workers who met American College of Sports Medicine recommendations was caused by insufficient frequency of physical efforts.